Students Perceptions of The Implementation of Occupational Safety and Health Work on Wood Working Practices - Putra, Dion Dwi; Abdullah, Rijal (CIVED, 2024)
The lack of knowledge and how to use tools when practicing can cause work accidents that harm students and schools that make this research raised. Occupational safety and health are mandatory things at work, which is the main step before starting the activity, so that students can understand the meaning of occupational safety and health itself. The purpose of this study was to reveal students' perceptions of the application of occupational safety and health in Woodworking Practices in the Class XI DPIB Workshop of SMK Negeri 1 West Sumatra. A descriptive research model was used in a quantitative approach. The product was validated by two experts and 30 students who took Woodworking Practice subjects in the July–December 2023 semester. Based on the validation that has been carried out by material expert 1, the result is 80% with good criteria; material expert 2 obtained a result of 81% with good criteria. Based on the results of this study, it can be concluded that students' perceptions of the application of occupational safety and health in woodworking practices in workshops that use descriptive research with quantitative.